2018
DOI: 10.1021/acs.jpca.7b10318
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Hydrogen Peroxide with Br and I Atoms

Abstract: The reaction mechanisms of Br and I atoms with HO have been investigated using DFT and high-level ab initio calculations. The H-abstraction and OH-abstraction channels were highlighted. The geometries of the stationary points were optimized at the B3LYP/aug-cc-pVTZ level of theory, and the energetics were recalculated with the coupled cluster theory. Spin-orbit coupling for each halogenated species was also explicitly computed by employing the MRCI level of theory. Thermochemistry for HOBr and HOI has been rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
3
6
0
Order By: Relevance
“…The final level of theory is denoted as CCSD­(T)/CBS + ΔCV + ΔSO + ΔPP + ΔZPE. We have applied this approach previously in a series of papers on atmospheric reactivity of halo-hydrocarbons and a similar approach in previous work on mercury compounds . The counterpoise correction for the estimation of the basis set superposition error was not taken into account because several previous works showed that it could lead to discrepancies in the energetic results. …”
Section: Computational Methodsmentioning
confidence: 99%
“…The final level of theory is denoted as CCSD­(T)/CBS + ΔCV + ΔSO + ΔPP + ΔZPE. We have applied this approach previously in a series of papers on atmospheric reactivity of halo-hydrocarbons and a similar approach in previous work on mercury compounds . The counterpoise correction for the estimation of the basis set superposition error was not taken into account because several previous works showed that it could lead to discrepancies in the energetic results. …”
Section: Computational Methodsmentioning
confidence: 99%
“…In the present work, density functional theory (DFT) calculations were conducted to explore the regions of potential energy surface (PES) relevant to n ‐C 3 F 7 I dissociation. Following Fortin et al., the geometries of stationary points on the PES were optimized with the B3LYP DFT functional in conjunction with the correlation consistent polarized triple zeta basis set cc‐pVTZ‐PP of Peterson et al. with the pseudopotential for the core electrons of heavy atoms .…”
Section: Resultsmentioning
confidence: 99%
“…These estimations generated too much uncertainties to be taken into account. It was recently demonstrated for the reactions of halogen atoms with hydrogen peroxide (Fortin et al, 2018). A strong influence of the nature of the halogen atom on the rate constant at 298 K was shown with a change in the values of about twelve orders of magnitude when going from chlorine to iodine.…”
Section: Iodine Mechanism and 0d Model Presentationmentioning
confidence: 90%
“…If it's not the case, the selected values correspond to the most recent experimental data. When reactions are missing, an examination of the theoretical works available in the literature (Bai et al, 2015;Canneaux et al, 2010;Cours et al, 2013;Fortin et al, 2018;Gómez Martin et al, 2013;Hammaecher et al, 2011;Kaltsoyannis and Plane, 2008;Khanniche et al, 2016b;Louis et al, 2011;Saiz-Lopez et al, 2016;Xerri et al, 2012) was performed and the corresponding thermokinetic data was added to the mechanism.…”
Section: Iodine Mechanism and 0d Model Presentationmentioning
confidence: 99%